Pelatihan Peningkatan Mutu Penelitian Tindakan Kelas Guru-Guru SMP Kecamatan Pinggir Kabupaten Bengkalis - Sakdanur Nas; Isjoni; M. Yogi Riantama; Riki Apriyandi (Pucuk Rebung: Jurnal Pengabdian kepada Masyarakat, 2021)
The purpose of this service is to provide understanding and experience about CAR writing to Pinggir Middle School teachers. It is hoped that with this service, all Pinggir Middle and High School teachers can carry out CAR writing as a teacher's scientific work later. The target of this service is teachers whose promotion is constrained due to the absence of research as their scientific work. It was concluded that there were still many teachers who did not understand the nature of this Classroom Action Research (CAR). This is because in general teachers are not used to writing CAR, even if teachers who have participated in PLPG are given CAR material, but the allocation provided does not allow them to be able to master CAR. One thing that teachers can do is imitate the CAR reports that have been made by previous teachers. So that it seems to just adapt from other people's research reports. At the beginning and until the end of the 4 days (32 hours) most of them understood and the motivation to produce the product was quite high. When carrying out the activities, no one did not understand, and sincerity was seen from time to time in both group and classical discussions. At the end of the service activity, each teacher is required to insert a product in the form of a proposal, which consists of Chapter I Introduction, Chapter II Literature Review, and Chapter III Research Methods. And Bibliography.